2010
DOI: 10.1158/0008-5472.can-09-1707
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of CD133+ and CD133− Glioblastoma-Derived Cancer Stem Cell Lines Suggest Different Cells of Origin

Abstract: Glioblastoma multiforme (GBM) is paradigmatic for the investigation of cancer stem cells (CSC) in solid tumors. Growing evidence suggests that different types of CSC lead to the formation of GBM. This has prompted the present comparison of gene expression profiles between 17 GBM CSC lines and their different putative founder cells. Using a newly derived 24-gene signature, we can now distinguish two subgroups of GBM: Type I CSC lines display "proneural" signature genes and resemble fetal neural stem cell (fNSC)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
245
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(258 citation statements)
references
References 41 publications
13
245
0
Order By: Relevance
“…In parallel, some studies suggested that there are also different subtypes of GSCs and identified two different subtypes of GSC: proneural type and mesenchymal type [82][83][84]. In the studies of Mao et al [82] and Bhat et al [83], Olig2 is recognised as a marker of proneural GSC.…”
Section: Discussionmentioning
confidence: 98%
“…In parallel, some studies suggested that there are also different subtypes of GSCs and identified two different subtypes of GSC: proneural type and mesenchymal type [82][83][84]. In the studies of Mao et al [82] and Bhat et al [83], Olig2 is recognised as a marker of proneural GSC.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the SP may or may not enrich BTSCs [63,73]. Furthermore, although it has been reported (or assumed) that there exists a lineage relationship between CD133 + and CD133 -brain tumor cells, the two populations of cells may have different cells-of-origin [70]. More studies are required to resolve these contradictory findings.…”
Section: Csc Heterogeneitymentioning
confidence: 99%
“…CSCs have been reported in brain tumors, especially in glioblastoma multiforme (GBM) [61][62][63][64][65][66][67][68][69][70][71][72][73][74]. The stemlike GBM cells have been enriched using cell surface molecules, such as CD133 [61,72], SSEA-1 (stagespecific embryonic antigen-1) [64], EGFR [67,68], and CD44 [69], or functional assays, including the SP analysis [7,63,73] and neurosphere assays [49,74].…”
Section: Csc Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because stem cells and tumor cells self-renew, they likely share similar signals to mediate this event. The role of Wnt signaling in GBM is a developing topic with a limited number of studies implicating this pathway in gliomagenesis [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%